Les systèmes graphiques du francoprovençal : état des lieux et perspectives - Michela Russo; Dominique Stich (Lengas)
In the Francoprovençal domain there is not a unitary orthographic system. Several transcriptions have been proposed on a phonetic basis, and the principle of a grammatical and etymological spelling is generally not supported.An orthographic system that takes into account the entire Francoprovençal domain, France, Switzerland and Italy has been proposed by Dominique Stich (1998 ; 1999 ; 2001 ; 2003). It is a morphological and archaic writing system inspired by the French and Occitan systems. We will present this supra-dialectal graphic system which is today called O. R. B., abbreviation of: reference spelling B. In this article we want to clarify the relationships between the different Francoprovençal orthographic systems in use today and to indicate the reasons that can motivate the use of a supra-dialectal orthographic unitary system. We will see samples transcribed in O. R. B. from 18th century Lyonnais texts.By studying the relationships between supra-dialectal writing and the phonological system in the frame of this type of Lyonnais texts, we will be able to propose phonologically inclusive choices in relation to very localized written micro-variations.We will focus particularly on the orthographic transcription and the phonological diasystem of palatal consonants, which are very complex from a phonological point of view in Francoprovençal.